Perfect word. - Tan, Junming. (2011)
The fiction is set in contemporary Singapore with the recent General Elections 2011 as the backdrop. The main character, a male, is a copywriter that works at an advertising agency. He used to have dreams about being a writer/poet but now has become an average joe and uses what little talent he has left to earn a living. He is disillusioned with life and falls into the same routine for many years. However, one day his boss tells him to change a word on his copy. However, when he was unable to find the correct word, his boss tells him that he has lost the word and must find it. Thus, the narrator begins his search for the word he has lost across different parts of Singapore.